Detection Method for Salmonella Typhimurium and Salmonella Enteritidis using Real-Time Polymerase Chain Reaction - Nurjanah, Siti; P. Rahayu, Winiati; Al Mutaqin, Lisa (International Journal of Engineering and Technology, 2019)
Salmonella is a pathogenic bacterium that can cause serious harm to humans. Chicken carcasses have been reported contaminated by Salmonella, especially S. Typhimurium and S. Enteritidis. These two serovars are very difficult to be confirmed and distinguished using biochemical analysis, therefore a rapid method for detection and differentiation of both is required. The objective of this study was to evaluate designed primer for detection and differentiation of S. Typhimurium and S. Enteritidis on chicken carcasses using real time Polymerase Chain Reaction (rt-PCR). Detection of Salmonella spp. was conducted using primer sequence from invA gene. Differentiation of both Salmonella serovars was conducted using specific target gene from S. Typhimurium (STM) and specific virulence plasmid of S. Enteritidis (Prot6E). The result showed that invA primer effective to detect all species Salmonella tested and has good specificity that could not detect Escherichia coli and Shigella dysenteriae in the similar melting temperature.   Two specific primers STM and prot6E have distinguished between S. Typhimurium and S. Enteritidis.  Sensitivity of method showed very good with 0.5 μM primer concentration of invA, STM and prot6E that were 0.2 pg, 22 pg and 28 pg respectively. Initial trial showed that this method can be applied for detection of Salmonella spp. and two serovars in chicken carcasses.